Exo+ proofreading polymerases mediate genetic analysis and its application in biomedical studies - LIAO Duan-fang; CHEN Lin-ling; PENG Cui-ying; ZHANG Jia; LI Kai (Acta Pharmacologica Sinica, 2016)
Polymerases with a proofreading function in their internal 3´ to 5´ exonuclease possess high fidelity for DNA replication both in vivo and in vitro. The obstacle facing Exo+ polymerases for single nucleotide polymorphism (SNP) detection could be bypassed by using primer-3´-termini modification. This hypothesis has been well tested using three types of modified allele specific primers with: 3´ labeling, 3´ to 5´exonuclease resistance, and 3´dehydroxylation. Accordingly, three new SNP assaying methods have been developed to carry out genome-wide genotyping, taking advantage of the enzymatic properties of Exo+ polymerases. These new mutation detection assays are widely adaptable to a variety of platforms, including multi-well plate and microarray technologies. Application of Exo+ polymerases to genetic analysis, including genotyping that is mostly relevant to pharmacogenetics, high-fidelity gene expression profiling, rare mutation detection and mutation load assay, will help to accelerate the pace of personalized medicine. In this review paper, we will first introduce three new assays that we have recently developed, and then describe a number of their applications in pharmacogenetics and in other biomedical studies.